1HNMR-based metabonomic study of sub-chronic hepatotoxicity induced by realgar. (4th November 2016) - Huo, Taoguang; Fang, Ying; Zhao, Longshan; Xiong, Zhili; Zhang, Yinghua; Wang, Yanlei; Feng, Cong; Yuan, Mingmei; Wang, Shouyun; Chen, Mo; Jiang, Hong
Abstract: Ethnopharmacological relevance: Realgar has been used as a traditional Chinese medicine (TCM) for thousands of years. Recently, a number of realgar or realgar-containing medicines poisoning cases have been reported. However, the toxicological mechanism of realgar has not been clearly clarified. In present study, the subchronic hepatotoxicity of realgar on mice was investigated using 1 HNMR-based metabonomic approaches. Materials and methods: Twenty-eight male mice were divided into control group and low (0.15 g/kg), middle (0.45 g/kg), high (1.35 g/kg) dosage realgar exposed groups. Their plasma and urine samples were used for NMR spectroscopic metabolic profiling. Principal component analysis (PCA) and pathway analysis were used to detect the hepatotoxic effects of realgar. Liver histopathological examination and plasma clinical chemistry analyses were also performed. Results: Plasma clinical chemistry analyses showed increased levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total protein (TP), total cholesterol (TC) and choline esterase (CHE) in realgar-exposed mice indicating liver injury. The PCA score plots showed the metabolic profiles of realgar-exposed mice apparently separated from the controls. Obvious dose-dependent changes of metabolites in urine and plasma of realgar-exposed mice were observed. From the loading plots and boxplots results, the concentrations of VLDL/LDL, 3-HB, lactate, acetate, acetoacetate, creatine, glutamate, methionine, NAc, TMAO, alanine in plasma and pyruvate, succinate, 2-oxoglutarate, DMA, citrate, hippurate, glycine, taurine, phenylalanine, lactate in urine were significantly changed in realgar-exposed mice. The change trends of metabolites in urine and plasma from mice sub-chronic exposed to realgar are similar to those reported in rats acute exposed to realgar, which indicate the acute and sub-chronic toxic mechanism of realgar are same. The disturbed metabolic pathway include energy metabolism, amino acids metabolism and gut bacteria metabolism. Conclusions: The present work illustrated the NMR-based metabonomic approach can capture and probe the metabolic alterations induced by traditional Chinese medicine in the toxicological effects. Graphical abstract: